F, 57-4.(x+1)²=21 G, (x-3)(2x-4)=0 H, x.(x-7)=0 i, 4 mũ x+¹+4mũ x =80

F, 57-4.(x+1)²=21

G, (x-3)(2x-4)=0

H, x.(x-7)=0

i, 4 mũ x+¹+4mũ x =80

2 bình luận về “F, 57-4.(x+1)²=21 G, (x-3)(2x-4)=0 H, x.(x-7)=0 i, 4 mũ x+¹+4mũ x =80”

  1. f, 57-4(x+1)^2 = 21
    => 4(x+1)^2 = 57-21
    => 4(x+1)^2=36
    => (x+1)^2=36:4
    => (x+1)^2=9
    => [((x+1)^2=3^2),((x+1)^2=(-3)^2):}
    => [(x+1=3),(x+1=-3):}
    => [(x=2),(x=-4):}
    Vậy x = 2,x=-4
    g, (x-3)(2x-4)=0
    => [(x-3=0),(2x-4=0):}
    => [(x=0+3),(2x=0+4):}
    => [(x=3),(2x=4):}
    => [(x=3),(x=4:2):}
    => [(x=3),(x=2):}
    h, x(x-7)=0
    => [(x=0),(x-7=0):}
    => [(x=0),(x=0+7):}
    => [(x=0),(x=7):}
    Vậy x=0,x=7
    i, 4^(x+1)+4^x=80
    => 4^x*4^1+4^x*1=80
    => 4^x(4^1+1)=80
    => 4^x*5=80
    => 4^x=80:5
    => 4^x=16
    => 4^x=4^2
    => x = 2
    Vậy x = 2

    Trả lời
  2. Giải đáp:
     
    Lời giải và giải thích chi tiết:
    F,57-4.(x+1)^2=21
            4.(x+1)^2=57-21
            4.(x+1)^2=36
               (x+1)^2=36:4
               (x+1)^2=9
               (x+1)^2=(+-3)^2
    ta có 2 trg hp :
    =>x+1=3    =>x=3-1   =>x=2
         x+1=-3       x=-3-1       x=-4
    =>x thuộc {2,-4}
    —————————————
    G,(x-3).(2x-4)=0
    ta có 2 trg hp :
    th1 : x-3=0
                x=0+3
                x=3
    th2 : 2x-4=0
            2x=0+4
            2x=4
              x=4:2
              x=2
    ——————-
    H,x.(x-7)=0
       x.x-7=0
       x-1.x-7=0
       x.(-1-7)=0
       x.(-8)=0
             x=0:(-8)
             x=0
    ——————-
    i,4^x+1+4^x=80
     4^x.4^1+4^1.1=80
    4^x.(4^1+1)=80
    4^x.(4+1)=80
    4^x.5=80
    4^x=80:5
    4^x=16
    4^x=4^2
    =>x=2

    Trả lời

Viết một bình luận

Câu hỏi mới